Share repurchase and cash dividend - Substitute or complement? Analysis from the Vietnam securities market - Dang Trung Kien; Yi-Pei Chen (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of this report was to assess the relationship among the cash dividend payout and share repurchase, through essential cash distribution methods adopted by Vietnamese publicly listed companies. The complementary along with substitute relationship from these financial practices might contribute to determine the financial managerial behavior in Vietnam as a leading development emerging market within Asia Pacific area. Design/methodology/approach: The research applied regression analysis technique to determine the nonlinear relationship among the share repurchase and cash dividend. Findings: The research found the nonlinear relationship among the change in dividend along with the repurchase yield. Moreover, the research found a significant positive correlation which reveals the prominent of complementary impact in the complete sample. The results and estimations of the research are consistent in robustness tests. There is a nonlinear relationship between the change in dividend and the repurchase yield. In addition, a significantly positive correlation reveals the dominant of complementary effect in the whole sample. The results are consistent in robustness tests. Research limitations/implications: It is crucial to ensure that there is an essential scope for the enhancement which remains and it is a component of the future study such as the influence of the stock dividend through various practice while companies are partly dominated or effected by the government, through the characteristics as the emerging markets such as Vietnam, as they are interesting topics which need further study. Originality/value: Through a comprehensive analysis, the study outcomes propose that Vietnamese listed companies should meticulously assess their future growth concerning share repurchase and other capital distribution activities. This strategy should take into account the involvement of various stakeholders and their benefit.
Keywords: 650; Share repurchase; cash dividend; Vietnamese stock market; Substitute; Complement